TAHAPAN PERENCANAAN DAN ESTIMASI BIAYA PADA PROYEK PEMBANGUNAN BANGUNAN GEDUNG NEGARA - Evan Evan; Wita Kristiana; Dewantoro Dewantoro (Universitas Lambung Mangkurat, 2021)
Planning is an important and vital function in construction development activities, therefore a building requires the stages of construction of a State Building which is something that must be understood thoroughly and in-depth. Considering that the stages of the construction of a State Building were previously only intended for buildings financed by financial resources from the APBN, since the issuance and promulgation of Presidential Regulation Number 73 of 2011 concerning the Construction of State Building that all buildings whose construction is financed from funding sources both from the APBN and from the APBD must comply with the provisions regulated by the Presidential Regulation. Understanding of the stages of the construction of State Buildings is important, considering that this stage is a sequence of processes that are closely related to the fulfillment of administrative and technical requirements for State Buildings, so that state buildings are state/regional property for official purposes and as venues for the event of government apparatus activities which must be functional, meet building safety, and the development implementation process is carried out in an orderly, effective, efficient, economical, not excessive, and environmentally friendly. This study aimed to find how to carry out technical planning along with the stages and how much was the estimated cost for planning the expansion and arrangement of library service buildings. From the research results, it can be concluded that technical planning produced documents in the form of 1) preparation stage reports; 2) report on the stages of the planning concept; 3) pre-planning stage documents; 4) document development stages of plans and detailed plans for buildings. The estimated cost for each component was divided into 5 divisions, namely the R3K division for Rp. 28,727,500.00, sitework division for Rp. 228,326,761.05, structural division for Rp. 1,769,109,715.79, architectural division for Rp. 1,661,172,550.79, and electrical, mechanical, and plumbing division for Rp. 260,391. 160.28, then the total amount was added with 10% VAT and was rounded up, so that the Total Cost Budget Plan was Rp. 4,342,000,000.00 (four billion three hundred forty-two million and five hundred thousand rupiah).